Research of indirect advertising in video game industry - Stavljanin, Velimir; Cvijović, Jelena; Kostić-Stanković, Milica (Industrija, 2017)
Product placement or indirect advertising, and video games are two very current themes. There are more and more video game users in the world, and fewer are those who have confidence in traditional forms of advertising. In order to reach a larger number of consumers, product placement is increasingly used today, and product placement in video games is becoming an increasingly attractive field of action. Although there are numerous studies in the field of the application of product placement in video games, authors have so far not been concerned with studying the way different motivation for playing influences the acceptance of product placement and whether, depending on the type of motivation, the effects of product placement would be different. This will allow better targeting of video game players and increasing product placement efficiency in video games. This paper examines whether different categories of primary motivation can affect the product placement effects, and whether players’ attitudes towards product placement differ, depending on the primary motivation.